REGULASI TERHADAP BENTUK JAMINAN KEBENDAAN ATAS PESAWAT TERBANG SEBAGAI OBYEK JAMINAN HUTANG DALAM KREDIT PERBANKAN - Mahasiswa Fakultas Hukum Universitas Sebelas Maret, Getar Danishswara Anugrah Akbar Darmawan (MAJALAH ILMIAH GEMA, 2014)
This research aims to determine the form of property rights of aircraft according to national regulations and international regulations as well as the form of engagement imposed on aircraft objects in bank credit. This research used a qualitative approach with sociological or empirical research because it involves the engagement imposed on aircraft objects in bank credit. This study examined secondary data initially, and then proceed with a study of primary data in the field. Primary data is sourced from bank staff legal department. Secondary data was sourced from secondary data in the field of law. For primary data types, data collection was done in two ways, namely, observation and interview. Secondary data collection is done through literature study and analysis of documents, archives, primary legal materials and secondary legal materials. From the discussion of the results of the study produced two (2) following conclusions: First, the form of property rights over the aircraft object is of international importance in the article 71 act No.1 of 2009 art according to Aviation that are subject to cape town convention and its protocol. Because Indonesia has ratified the convention with presidential decree No. 8 of 2007, so that its implementation must be in accordance with the convention. Keywords: Property Rights, Aircraft, Collateral